2017
DOI: 10.1097/nor.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nurses' Intentions to Administer As-Needed Opioid Analgesics for Pain Relief to Postoperative Orthopaedic Patients in the Acute Care Setting

Abstract: The study showed that the IBM constructs are useful for predicting intentions toward performance of a professional behavior. The inclusion of self-efficacy, underlying beliefs, and salience of the behavior was new and unique contributions to the existing body of knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The study's result interestingly contradicted the results by [20], who argued that increasing the salience of product transformationwhich involved recyclables being transformed into new items-led to the increase in recycling behaviour. Moreover, the results did not match the findings of [32], who examined the IBM factors to check which factor could predict nurses' intentions to deliver "as required" pain relief medications. They found that salience of behaviour was the only significant predictor for the nurses' intentions.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The study's result interestingly contradicted the results by [20], who argued that increasing the salience of product transformationwhich involved recyclables being transformed into new items-led to the increase in recycling behaviour. Moreover, the results did not match the findings of [32], who examined the IBM factors to check which factor could predict nurses' intentions to deliver "as required" pain relief medications. They found that salience of behaviour was the only significant predictor for the nurses' intentions.…”
Section: Discussionmentioning
confidence: 66%
“…A study conducted by Taylor et al [32] attempted to determine which main IBM factor was able to predict nurses' intentions to provide pain relief medicines that were taken "as needed" (commonly known as PRN) to hospitalised postoperative orthopaedic patients. The research showed that IBM structures were beneficial in predicting intentions towards performing a professional's behaviour.…”
Section: Salience Of Behaviourmentioning
confidence: 99%